Molecular docking and structure-activity relationship studies on benzothiazole based non-peptidic BACE-1 inhibitors - Xu, W.; Chen, G.; Zhu, W.; Zuo, Zhili (Pergamon, 2010)
A similarity search on the structural analogs of an inhibitor of BACE-1 with IC50 2.8 μM, which contained a P1 benzothiazole group together with a triazine ring linked by a secondary amine group, was described in this Letter and some more potent inhibitors against BACE-1 were identified. The most potent compound 5 (IC50 = 0.12 μM) increases the inhibitory potency by 24 folds. Our results suggest that a pyrrolidinyl side group at the P3′ and P4′ of the inhibitors are favored for strong inhibition and a small aromatic group at the P4 position is also essential to the potency.